ELOTUZUMAB FOR THE TREATMENT OF RELAPSED OR REFRACTORY MULTIPLE MYELOMA, WITH SPECIAL REFERENCE TO ITS MODES OF ACTION AND SLAMF7 SIGNALING - Masafumi Taniwaki; Mihoko Yoshida; Yosuke Matsumoto; Kazuho Shimura; Junya Kuroda; Hiroto Kaneko (Mediterranean Journal of Hematology and Infectious Diseases)
Elotuzumab, targeting signaling lymphocytic activation molecule family 7 (SLAMF7), has been approved in combination with lenalidomide and dexamethasone   (ELd)   for relapsed/refractory  multiple myeloma (MM) based on the findings of the phase III randomized trial  ELOQUENT-2 (NCT01239797). Four-year  follow-up  analyses  of  ELOQUENT-2 have demonstrated  that  progression-free survival was 21%  in  ELd  versus  14%  in  Ld. Elotuzumab binds a unique epitope on the membrane IgC2 domain of SLAMF7, exhibiting a dual mechanism of  action:  natural  killer  (NK)  cell-mediated  antibody-dependent  cellular  cytotoxicity  (ADCC) and  enhancement  of  NK  cell  activity.  The  ADCC  is  mediated  through  engagement  between  Fc portion  of  elotuzumab  and  FcgRIIIa/CD16  on  NK  cells. Enhanced NK cell cytotoxicity results fromm phosphorylation  of  the  immunoreceptor  tyrosine-based  switch  motif  (ITSM)  that  is induced via elotuzumab binding and recruits the SLAM-associated adaptor protein EAT-2.The coupling of EAT-2 to the phospholipase Cg enzymes SH2 domain leads to enhanced Ca2+. Influx and MAPK/Erk pathway activation, resulting in granule polarization and enhanced exocytosis inNK  cells. Elotuzumab  does not stimulate the  proliferation of MM cells due to a lack of EAT-2.The  inhibitory  effects  of  elotuzumab  on  MM  cell  growth  are  not  induced by  the lack  of  CD45, even  though  SHP-2,  SHP-1,  SHIP-1,  and  Csk may be  recruited  to  phosphorylated  ITSM  of SLAMF7.  ELd  improves PFS in patients  with  high-risk  cytogenetics,  i.e.  t(4;14),  del(17p),  and 1q21  gain/amplification. Since  the immune  state  is  paralytic  in  advanced  MM,  the  efficacy  of ELd with minimal toxicity may bring forward for consideration of its use in the early stages of the disease.